A reliable and sensitive time-resolved fluorescent immunochromatographic assay (TRFICA) for ochratoxin A in agro-products. (January 2015) - Majdinasab, Marjan; Sheikh-Zeinoddin, Mahmoud; Soleimanian-Zad, Sabihe; Li, Peiwu; Zhang, Qi; Li, Xin; Tang, Xiaoqian; Li, Jing
Abstract: Immunochromatographic assays (ICAs) are considered as a suitable diagnostic tool for the detection of mycotoxins. Mycotoxins and especially, ochratoxin A are analytes with more demanding sensitivity requirements. To enhance the sensitivity of current immunochromatographic assays for ochratoxin A (OTA), a novel sensitive ICA was developed in this study. In the assay, microspheres enclosing fluorescent europium (III) [Eu(III)] nanoparticles (EuNPs) were used as a label for OTA monoclonal antibody (OTA-mAb) conjugation. Accordingly, assay was called time-resolved fluorescent immunochromatographic assay (TRFICA). The test strip was composed of three parts: a sample pad, nitrocellulose membrane and an absorbent pad. As for detection, a proper concentration of conjugated microspheres was pipetted into the microtube and sample extract was added to it. Then the strip was inserted into the tube and the fluid flow along the strip. The TRFICA results were obtained in 8 min and read by a portable TRFICA strip reader. The established method allows quantitative determination of OTA with limit of detection as low as 1.0 μg kg −1 in the samples. For validation, spiked samples including wheat, maize, soybean and rice were respectively assayed by TRFICA and a standard high performance liquid chromatography equipped with a fluorescence detector (HPLC-FLD), and good agreement of results was obtained between two methods. Highlights: Developing a time-resolved fluorescent immunochromatographic assay for ochratoxin A. Using antibody conjugated fluorescent europium nanoparticles as label for detection. The assay was used for ochratoxin A detection in agro-products. The assay sensitivity increased compared to gold nanoparticles. The results were reliable and in accordance with those obtained using HPLC.